1981
DOI: 10.1128/aem.42.3.389-393.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aflatoxin B1 on chromatin-bound ribonucleic acid polymerase and nucleic acid and protein synthesis in germinating maize seeds

Abstract: The treatment of germinating maize seeds (cv. Ganga 2) with aflatoxin B1 resulted in suppression of ribonucleic acid (RNA), protein, and deoxyribonucleic acid (DNA) synthesis at 3, 4, and 5 h, respectively. At or below the concentrations inhibitory for these in vivo syntheses, the toxin inhibited chromatin-bound DNAdependent RNA polymerase activity. The synthesis of both polyadenylated and non-polyadenylated RNA was inhibited, but the effect on the former was more pronounced. Equilibrium dialysis and differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Thus, Ca 2þ ions reduce the toxic effect of Cd 2þ on broad bean seedling. Other investigators have noted the similar protective effect of Ca 2þ against toxic effects of Cd 2þ (Agar and Taspinar, 2003;Busby and Wogan, 1985;Neal, 1987;Tripathi and Misra, 1981).…”
Section: Discussionmentioning
confidence: 66%
“…Thus, Ca 2þ ions reduce the toxic effect of Cd 2þ on broad bean seedling. Other investigators have noted the similar protective effect of Ca 2þ against toxic effects of Cd 2þ (Agar and Taspinar, 2003;Busby and Wogan, 1985;Neal, 1987;Tripathi and Misra, 1981).…”
Section: Discussionmentioning
confidence: 66%
“…In mice fed for 4 weeks using maize contaminated with mycotoxin (ZEA, aflatoxin, and DON), the oocyte histone methylation and DNA methylation changed [203]. (h) RNA polymerase effects: AFB1 has inhibitory effects on chromatin-bound RNA polymerase, which is DNA-dependent, and consequently interferes with synthesis of RNA [204,205]. Luteoskyrin and patulin also inhibit RNA polymerase [204,205].…”
Section: Action Mechanisms Of Mycotoxins: Key Aspectsmentioning
confidence: 99%
“…(h) RNA polymerase effects: AFB1 has inhibitory effects on chromatin-bound RNA polymerase, which is DNA-dependent, and consequently interferes with synthesis of RNA [204,205]. Luteoskyrin and patulin also inhibit RNA polymerase [204,205]. (i) Necrosis and apoptosis: AFB1 cytotoxic effects in lymphocytes of humans involve necrosis, caspase activation, and apoptosis [206], which lead to programmed cell death and irreversible cell damage.…”
Section: Action Mechanisms Of Mycotoxins: Key Aspectsmentioning
confidence: 99%
“…As result of the GTS value, transcription and translation are affected. Previous studies found that AFB 1 affects GTS, polymorphism value, transcription and translation by binding to DNA in plant and animal organisms (Essigmann et al, 1982; Tripathi and Misra, 1981). This effect of AFB 1 on cells decreased after treatment with different concentration of Se 4+ + AFB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous articles about the effect of AFB 1 on higher plants indicated that it affects amino acid uptake, chlorophyll synthesis, germination of seeds, elongation of some plant roots and stems, protein synthesis, total carbohydrate and lipid content, RNA synthesis, chromosomal aberrations and the fidelity of DNA (Jones et al, 1980; Tripathi and Misra, 1981). Recently, several factors present in the foods of common consumption have been shown to modify these critical reactions of AFB 1 in animal (Bhattacharya et al, 1984).…”
Section: Introductionmentioning
confidence: 99%